Studies of therapeutic protein-containing patches for ocular delivery - Pow, Poh Yih (2016)
Research into thiolated chitosan hydrogel has increased over the last decade, due to its potential for use as a novel material in the design of controlled drug delivery systems. While multiple studies have been aimed towards drug release and timely degradation, limited studies have been done to investigate the enhancement of transporting anti-VEGF therapeutics from outside the eye, avoiding intravitreal injections. Hence, this report aims to demonstrate controlled and extended release of a bioactive anti-VEGF agent, such as ranibizumab, from different types of thiolated chitosan hydrogels with potential application in therapeutic mini-patches for the treatment of wet AMD. For the purposes of optimising patch design, two thiolated chitosan hydrogels, LChitosan-Cys and LChitosan-MNA respectively, have been characterised though analysis of the degree of thiolation, imaging using scanning electron microscopy (SEM), and individual swelling behaviour. Protien release profiles gathered show potential for controlling the duration and amount of release. Furthermore, hydrogel biodegradability was also examined, observing full degradation with 100% of protein release. These results, combined with the intrinsic properties of chitosan (e.g. mucoadhesion and permeation-enhancing effects) and the possibility of sustained protein release, suggest that thiolated chitosan hydrogels have promising applicability in ocular drug delivery systems.